2010
DOI: 10.1177/109258721001500203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Third-Generation Zoo Exhibit in Relation to Visitor Behavior and Interpretation Use

Abstract: This study, conducted over a four-year period at Chester Zoo in the UK, sought to evaluate the impact on visitor behavior and interpretation use that a transition from second- to third-generation zoo exhibit might affect. Visitors spent more time in the newer exhibit (even when allowing for relative floor area) and visitor time budgets suggest a high degree of visitor interaction with different exhibit elements. Specific interpretive elements were analyzed in detail, using quasi-quantitative methods in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“… [9] , [20] – [22] ); indeed it is reported that most zoos have active visitor research [23] , but publication of results appears relatively rare. More recently, a few studies have begun to assess how education goals are met [7] , [24] [27] , but these publications, in the specialist zoo and museum literature, do not appear to address the wider implications and importance of this kind of research. As zoos are starting to realise the wider scientific and social importance of their research into visitor behaviour, universities are realising the need to engage with the public and are looking for means to do so.…”
Section: Discussionmentioning
confidence: 99%
“… [9] , [20] – [22] ); indeed it is reported that most zoos have active visitor research [23] , but publication of results appears relatively rare. More recently, a few studies have begun to assess how education goals are met [7] , [24] [27] , but these publications, in the specialist zoo and museum literature, do not appear to address the wider implications and importance of this kind of research. As zoos are starting to realise the wider scientific and social importance of their research into visitor behaviour, universities are realising the need to engage with the public and are looking for means to do so.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this effort appear in a series of four articles published as a special issue in the Journal (2013-18(2)). Their study provided empirical Barrett et al (2017), Beck et al (2015), Benton andSinha (2011), Bixler et al (2015), Bourque et al (2014), Britt (2017), Burris (2019), Douglas et al (2018), Gilson and Kool (2019), Hall et al (2010), Ham (2013), Henker and Brown (2011), Knapp and Forist (2014), Lawhon et al (2017), Macklin et al (2010), Montero et al (2018), Morgan and Hwang (2014), Moss et al (2010), Ogle (2016), Stern (2013a, 2013b), Price et al (2018), Rahaman and Kian (2017), Reese (2013), Ren and Folta (2016),…”
Section: Interpretive Techniquesmentioning
confidence: 99%
“…Exhibit areas are designed including the topography and the types of plants in animals' natural environments and without including any boundary elements that distort the visual entegrity between animals and visitors 15,22,24,26,27 . Watching areas are outside the exhibit areas, which decreases the negative effect of crowds on animals and enable animals to exhibit more natural behaviors 23 . Therefore, animals are exhibited in a way that is suitable for their orginal habitats without destroying their social structure.…”
Section: Introductionmentioning
confidence: 99%